Role of Persuasion in Online Purchases: A Conceptual Framework - Ashok Mammen V; T. Bharathi (Journal of Corporate Finance Management and Banking System, 2024)
The trend towards online purchases continues to grow globally with significant increases in both the number of consumers and the volume of transactions. Indian e-commerce market is likely to show positive growth trend in the coming years. The study focuses on the role of persuasion and the factors related to attitude formation that leads to purchase intention among the population. The literature study covers online purchases, factors, time period from 1967 to present year. The identified variables for the study are marketer generated content, user generated content, social influence, trust, persuasion, attitude and purchase intention. The conceptual framework is proposed and is designed from the above select variables to understand the role of persuasion and its influence on attitude and purchase intention.